2002
DOI: 10.1002/jbm.10211
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion barriers of carboxymethylcellulose and polyethylene oxide composite gels

Abstract: Composite gels and films of CMC and PEO have been used to separate healing tissues and have been demonstrated to reduce postsurgical adhesions in animal models of adhesion formation. Gels of CMC/PEO were studied here to elucidate the mechanism by which the combination of PEO with CMC is effective in reducing adhesions between tissues. CMC and PEO were demonstrated to undergo micro phase separation to form a two-phase system. Protein partitioning was measured in this system for albumin, fibrinogen, and gamma gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 28 publications
0
32
0
2
Order By: Relevance
“…We hypothesized that hybridization of HA with other biocompatible polysaccharides that are not degraded enzymatically in humans could slow degradation while preserving HA's excellent biocompatibility. Cellulose derivatives such as carboxymethylcellulose (CMC) [12][13][14][15] and hydroxypropylmethyl cellulose (HPMC) [14] are also known to have good biocompatibility in the peritoneum. The biocompatibility of methyl cellulose (MC) in the peritoneum is not known, but the mixture of MC and HA has been reported to be biocompatible in intrathecal injection [16].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that hybridization of HA with other biocompatible polysaccharides that are not degraded enzymatically in humans could slow degradation while preserving HA's excellent biocompatibility. Cellulose derivatives such as carboxymethylcellulose (CMC) [12][13][14][15] and hydroxypropylmethyl cellulose (HPMC) [14] are also known to have good biocompatibility in the peritoneum. The biocompatibility of methyl cellulose (MC) in the peritoneum is not known, but the mixture of MC and HA has been reported to be biocompatible in intrathecal injection [16].…”
Section: Introductionmentioning
confidence: 99%
“…11,18,19,[23][24][25][26][27][28][29] Daha önceki çalışmalarda PEO+CMS'nin bağır-saklar üzerinde irritan olmadığı ve kuvvetli adezyon önleyici etkiye sahip olduğu gösteril-miştir. 3,11,18,24,26,27 Bizim çalışmamızda da bu maddelerin kuvvetli adezyon önleyici etkisinin olduğu görüldü. Kullanılan maddeler içinde adezyon skoru en az bulunan, hidroksiprolin düzeyini en fazla düşüren, fibroblastik aktiviteyi azaltan ve periserozal irritasyon yapmayan en kuvvetli adezyon önleyici etkinin PEO+CMS'de olduğu tespit edildi.…”
Section: Discussionunclassified
“…Calcium chloride inducing ionic cross-links is added to the formulation to create stronger interaction between the components. This modification prolongs the permanence of the product in the body because carboxymethil cellulose is otherwise rapidly resorbed 19,24 . Previous studies using Oxiplex have shown a significant reduction in the degree of postoperative peridural fibrosis 32 .…”
Section: Discussionmentioning
confidence: 99%